Modulation of sustained fear by transcranial direct current stimulation (tDCS) of the right inferior frontal cortex (rIFC) - Herrmann, Martin J.; Simons, Bibiane S. E.; Horst, Anna K.; Böhme, Stephanie; Straube, Thomas; Polak, Thomas (Biological Psychology, 2018)
Downregulation of emotional responses to threat is strongly associated with frontal cortex functions. Additionally pathological anxiety has been proposed to be associated with the altered frontal control. Understanding the frontal regulation of both initial and sustained fear responses seems to be crucial for further research on the treatment of anxiety disorders. Therefore, this study aims to examine the effects of transcranial direct current stimulation (tDCS) over the right inferior frontal cortex (rIFC) on the subjects’ psychophysiological responses as measured by skin conductance reaction (SCR) during a sustained threat paradigm. 80 participants were randomly assigned to an anodal and sham stimulation group in a double-blinded manner. Indicated by visual cues, participants anticipated the temporally unpredictable occurrence of aversive or neutral auditory stimuli. We found a significant interaction effect of condition x tDCS for SCR during the sustained threat. Post-hoc tests revealed a significant reduction in SCR during sustained fear in verum stimulated group. The results confirm that tDCS of the rIFC attenuates sustained fear. This supports the suggested role of the rIFC in psychophysiological emotional regulation and the potential use of tDCS to enhance these effects.
Created from Fastlane, Scopus look-up
Keywords: Right inferior frontal cortex (rIFC); Sustained fear; Transcranial direct current stimulation (tDCS); Unpredictable threat